Association of epicardial fat with noncalcified coronary plaque volume and with low attenuation plaque in people with HIV. (1st August 2021) - Sadouni, Manel; Durand, Madeleine; Boldeanu, Irina; Danieli, Coraline; Bodson-Clermont, Paule; Mansour, Samer; Baril, Jean-Guy; Trottier, Benoit; Tremblay, Cécile; Chartrand-Lefebvre, Carl
Abstract : Objectives: People with HIV are exposed to a higher risk of coronary artery disease (CAD) compared with the general population. Epicardial fat may play a unique role in promoting coronary atherosclerosis. We measured epicardial fat in participants living with HIV and controls and investigated its association with coronary plaque volume and low attenuation plaque, a marker of plaque vulnerability. Design: This is a cross-sectional study, nested in the Canadian HIV and Aging Cohort Study, a large prospective cohort actively following participants with HIV and controls. Participants with low/intermediate cardiovascular risk without symptoms/history of CAD were invited to undergo cardiac computed tomography (CT). Methods: Volume of epicardial fat, coronary plaque and low attenuation component of the plaque were measured. Association between epicardial fat, coronary plaque volume and low attenuation component was tested using adjusted regression analysis. Results: A total of 169 participants with HIV and 81 controls underwent cardiac CT. Participants with HIV had a greater epicardial fat volume compared with controls ( P  = 0.019). In participants with HIV, epicardial fat volume was positively associated with duration of nonnucleoside reverse transcriptase inhibitors (NNRTI) ( β =2.19, P  = 0.004). After adjustment for cardiovascular risk factors, epicardial fat volume was positively associated to noncalcified plaque volume [odds ratio (OR) = 1.09, P  = 0.028] and to the low-attenuation plaque component portion ( β =0.38, P  = 0.026). Conclusion: The association of epicardial fat volume to noncalcified plaque volume and to low attenuation component plaque may suggest a potential mechanism by which epicardial fat could be a silent driver of CAD in the HIV population. Abstract : Supplemental Digital Content is available in the text